Βιβλιοκρισία:A. KALDELLIS, Byzantine Readings of Ancient Historians. Texts in translation with introduction and notes [Routledge Classical Translations], New York 2015. - ΚΙΑΠΙΔΟΥ Ειρήνη-Σοφία (Byzantina Symmeikta, 2018)
Βιβλιοκρισία:A. KALDELLIS, Byzantine Readings of Ancient Historians. Texts in translation with introduction and notes [Routledge Classical Translations], New York 2015.